Allowable expenditures under the income tax law : the development of legal principles from the common law perspective - Sarafadeen, Nafiu Olaitan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
Allowable expenditure is a vital area available to taxpayers to explore for tax benefit.It is distinguishable from tax evasion, in the sense that the latter involves using unlawful means to circumvent the payment of taxes, it is therefore illegal and a crime punishable by the law; but allowable expenditure which may be described as an extended family member of tax avoidance is the process whereby taxpayers take advantage of legal opportunities to minimize their tax liability; the implication of this is that such taxpayers are knowingly trying to reduce their taxes, but they are not knowingly breaking the law. Allowable expenditure is an area of taxation law where the development of legal principles cannot be over emphasised as statutory provisions meant to control impermissible tax deduction may not cover all the schemes taxpayers and tax-lawyers (advisors) mechanically formulated for the purpose of tax benefit.This thesis addresses the issue of allowable expenditure in revenue law on which there are statutory provisions; it argues that in interpreting the statutes, the judiciary often comes up with legal principles relevant to this area of law. It is the development of these legal principles in relation to tax deduction of business expenses that the thesis evaluates, doing so from the perspective of common law jurisdictions.The concept of a loophole is an arresting proposition that illuminates revenue loss on the part of government, among other factors responsible for such loss. It hinders the tax authorities in carrying out their statutory duties of tax collections. In tax terminology, a loophole is defined as a technicality making it possible to circumvent the law's intent without violating the letter of the law; the thesis draws attention to the sophisticated schemes formulated by the taxpayers and their tax advisors to explore the loophole in the law for tax advantages. The thesis finds that the general consistency issue in impartiality of law requires that the principles sustaining the coherence of statutory framework, either on taxation or other legislative enactments, be observed when deciding, for instance, whether an expense is incurred for the purpose of producing income; hence the preference for interpretation that reduces the possibility of contradiction and inconsistencies among various statutory provisions. As a result of this finding, the thesis concludes that the ordinary principles of statutory construction must be applied to the words used by Parliament and this underscores the significance of interpretation of statutes. The thesis recommends that the principles of statutory construction should be upheld at all time and the implication of this is that a course of action that was designed to defeat the intention of Parliament should be treated as tax avoidance and dealt with accordingly since allowable expenditure as a tax benefit is meant for the deduction of expenses incurred in producing assessable income.